2019
DOI: 10.1002/lsm.23155
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Increases Viability in Full‐Thickness Grafts in Rats Submitted to Nicotine

Abstract: Background and Objectives Photobiomodulation (PBM) therapy with 830 nm wavelength or 660 wavelength to compare the effects with parameters of 30 mW, 0.028 cm2, 9.34 seconds, and 3.64 J on the total integration of total skin grafts in rats submitted to nicotine. Study Design/Materials and Methods Sixty male Wistar rats were divided in six groups: Sham—skin‐grafting surgery; 830 nm—skin‐grafting followed by 830 nm irradiation; 660 nm—skin grafting followed by 660 nm irradiation; Nicotine—subjected to subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Another parameter evaluated in this study was factor VIII, which is an essential coagulation factor that is synthesized from the vascular endothelium and released into the bloodstream. Factor VIII is an important indicator of vascularization and evaluates neovascularization by vascular density analysis (45). Emerging evidence suggested that oxidative stress-induced hypoxia triggered the process of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Another parameter evaluated in this study was factor VIII, which is an essential coagulation factor that is synthesized from the vascular endothelium and released into the bloodstream. Factor VIII is an important indicator of vascularization and evaluates neovascularization by vascular density analysis (45). Emerging evidence suggested that oxidative stress-induced hypoxia triggered the process of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PBM helps in angiogenesis, reducing the percentage of tissue necrosis and consequently increasing the viable area [6][7][8][20][21][22][23][24] . The parameters used in G5 coincide with the literature, which indicates the wavelength of 830 nm is more promising in neoangiogenesis and tissue healing 23 when compared to 630 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Another parameter we investigated in our study was factor VIII, which is an essential coagulation factor in glycoprotein structure that is synthesised from the vascular endothelium and released into the bloodstream. Factor VIII is an important indicator of vascularisation and provides evaluation of neovascularisation via vascular density analysis (de Souza et al., 2019). In our study, factor VIII levels were significantly higher in the nicotine group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Factor VIII is a glycoprotein that is synthesised from the vascular endothelium. It plays an essential role in blood clotting cascade and is used as an indicator of vascularisation via vascular density analysis (de Souza et al., 2019). The immunoreactivity of the factor VIII protein in the testicular tissues was determined using the avidin‐biotin‐peroxidase complex (Doganyigit, Okan, Kaymak, Pandir, & Silici, 2020).…”
Section: Methodsmentioning
confidence: 99%